The Evolution of My Extended SMAS-Biplanar Deep Plane Facelift to a Composite Tissue Deep Plane Face and Neck Lift: Similarities and Differences - Perkins, Stephen W.; Caniglia, Alexander (Facial Plastic Surgery)
Dr. Stephen Perkins, a seasoned facial plastic surgeon, presents his refined techniques in facelift surgery developed over four decades of practice. His evolution from traditional methods to the current composite tissue deep plane facelift is elucidated. His composite tissue deep plane facelift involves meticulous dissection and repositioning of the superficial musculoaponeurotic system (SMAS) and platysma in the deep plane, as well as incorporating his innovative "Perkins’ Kelly clamp anterior platysmaplasty." This technique, refined through years of experience, aims for natural, enduring results, crucially addressing patient concerns such as jowling and neck laxity. Long-term analysis reveals the advantages of Dr. Perkins’ technique, particularly in achieving sustained cervicomental angle improvement for over a decade postoperatively. This paper underscores the importance of understanding deep plane facelift techniques, distinguishing between different approaches, and tailoring surgical interventions to individual patient characteristics. Dr. Perkins’ comprehensive approach, incorporating advancements in surgical technique and meticulous patient care protocols, exemplifies the goal of achieving natural, long-lasting facial rejuvenation.